A transcription factor ensemble orchestrates bundle sheath expression in rice - Lei Hua; Na Wang; Susan Stanley; Ruth M. Donald; Satish Kumar Eeda; Kumari Billakurthi; Ana Rita Borba; Julian M. Hibberd (Nature Communications)
Abstract C4 photosynthesis has evolved in over sixty plant lineages and improves photosynthetic efficiency by ~50%. One unifying character of C4 plants is photosynthetic activation of a compartment such as the bundle sheath, but gene regulatory networks controlling this cell type are poorly understood. In Arabidopsis, a bipartite MYC-MYB transcription factor module restricts gene expression to these cells, but in grasses the regulatory logic allowing bundle sheath gene expression has not been defined. Using the global staple and C3 crop rice, we find that the SULFITE REDUCTASE promoter is sufficient for strong bundle sheath expression. This promoter encodes an intricate cis-regulatory logic with multiple activators and repressors acting combinatorially. Within this landscape we identify a distal cis-regulatory module (CRM) activated by an ensemble of transcription factors from the WRKY, G2-like, MYB-related, DOF, IDD and bZIP families. This module is necessary and sufficient to pattern gene expression to the rice bundle sheath. Oligomerisation of the CRM and fusion to core promoters containing Y-patches allow activity to be increased 220-fold. This CRM generates bundle sheath-specific expression in Arabidopsis indicating deep conservation in function between monocotyledons and dicotyledons. In summary, we identify an ancient, short, and tuneable CRM patterning expression to the bundle sheath that we anticipate will be useful for engineering this cell type in various crop species.